Environmental Sustainability Practices Leveraging Green Finance and Innovation for Enhance Eco-Friendly SMEs Performance - Joni Hendra; Khusnik Hudzafidah; Feni Wilamsari; Judi Suharsono (Penerbit Goodwood, 2026)
Purpose: This study examines how green finance and green innovation affect the business performance of environmentally conscious SMEs in East Java, particularly emphasizing the mediating role of environmental sustainability in promoting improved business outcomes while fostering sustainability. Research Methodology: The PLS-SEM method was used to analyze the business performance of 150 environmentally conscious SMEs in East Java. Results: This study indicates that both green innovation and green funding have a positive and significant impact on business performance. Green finance improves operational efficiency and market competitiveness. Meanwhile, green innovation greatly enhances a company's reputation and customer satisfaction, and the relationship between green finance, green innovation, and business performance is mediated by environmental sustainability strategies Conclusions: The results show that SME company performance is shaped by a synergistic relationship. Sustainability methods improve corporate success by strengthening green financing and innovations. Limitations: This research is limited to 150 environmentally friendly batik SMEs in East Java; therefore, the results may not be generalizable to other industrial sectors or regions. Contributions: These findings have significant ramifications for politicians and business practitioners advocating the use of green finance and innovation to achieve commercial and environmental sustainability.